Analysis of the results of combined treatment of cervix precancerous pathology in reproductive aged women - I.Z. Gladchuk; I.Z. Gladchuk; N.M. Kashtalian (Publishing House TRILIST, 2021)
Aim of the study. Comparative analysis of the results of cervical epithelial neoplasia (CIN) I and II levels (p16ink4a-negative) (LSIL in LAST terminology) treatment against the background of highly oncogenic HPV infection using cold plasma ablation and immunomodulatory therapy with Аllokin-alpha. Materials and methods. We examined 60 women who received treatment for CIN I and CIN II (p16ink 4A negative) at the Multidisciplinary Medical Center of Odessa National Medical University. All women were of reproductive age, had mild dysplasia, high-risk HPV infection (HPV 16, 18, 31, 45) and histological confirmation of CIN I and CIN II (p16ink 4A negative). The patients were divided into 2 groups: 1 (main) group consisted of 30 women who received cold plasma ablation of cervical dysplasia in combination with immunomodulatory therapy with Аllokin-alpha (1 mg subcutaneously every other day, 3 injections before surgery and 3 injections after ablation), Group 2 (control) consisted of 30 patients who received standard cold plasma ablative treatment without prescribing immunomodulators. All women underwent cytomorphological examination of the cervical epithelium, HPV testing by RealTime PCR and colposcopy with mandatory targeted biopsy at the preoperative stage. Results. The use of combined cold plasma ablative treatment of CIN I and CIN II (p16ink 4A negative) in combination with the administration of the immunomodulator Аllokin-alpha significantly reduced the duration of discharge after ablation to 5.44 ± 1.03 days (95% CI: 4.96-6.05), the timing of epithelialization is up to 29.31 ± 1.12 days (95% CI: 26.81-32.32), and to exclude cases of recurrence of genital warts and cervical keratosis. Chances of HPV elimination 6 months after treatment (OR - 5.48; 95% CI: 1.56-29.03; p = 0.0075) and 12 months after treatment (OR - 15.48; 95% CI : 2.05-136.45; p = 0.0094), significantly higher with the combined with immunomodulation method of treatment, in contrast to only cold plasma ablation. Conclusion. Combined, with the use of cold plasma ablation and immunomodulation by perioperative management of Аllokin-alpha, LSIL treatment against the background of highly oncogenic HPV infection in women of reproductive age is accompanied by better functional results, compared with the use of cold plasma ablation alone: reduction in the duration of discharge, acceleration of epithelialization, normalization of the colposcopic and cytologic picture, decrease in the frequency of relapses, a significant increase in the frequency of HPV elimination.